LA VIOLENCIA DE GÉNERO EN LOS ORDENAMIENTOS JURÍDICOS DE INSPIRACIÓN LATINA: (II) GLOBALIZACIÓN Y DISCRIMINACIÓN CONTRA LA MUJER - González Moreno, Juana María (2019)
These work represents the continuation of our titled study "The gender violence in the legal systems of Civil Law (I) Latin America versus Europe: discriminations of coming and going", presented in the Fifth European Conference on Feminist Investigation, "Gender and Power in New the Europe" (Lund, Sweden, August of 2003), and in which we try to illustrate, through the analysis of the Peruvian legal system, how the violence against the woman contained in the Latin American legal systems is bigger than the violence that the legal systems of European countries produces. In this second part, we show how the globalization has supposed a reinforcement of the contained in the different legal systems gender violence.